Are Padang City Branding Shaping Audience Consciousness: an Semiotics Analysis of Three Padang City Branding - Fitri Adona; Yusnani Yusnani; Sri Nita (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2018)
One form of city marketing that is currently developing is the provision of city image or city branding. Brands can have 6 levels of understanding namely attributes, benefits, cultural values, personality, and users. Cultural values are very different, especially around socially embedded issues such as status, gender, family, ethics, and customs. City branding helps influence "transfer of value" by establishing a relationship between what culture sees as a desired city and a particular product. This research is a study of the city branding of Padang city or a brand that is considered to belong to Padang City, namely "Padang Your Motherland", "Serenity of Minangkabau", and "Padang Taste". To what extent does three brand of  padang city  influence consumer awareness of the values of Minangkabau culture that is dominantly adopted by the people of Padang City? Semiotic analysis and personal interviews were used to answer this research question. Some consumers are less aware of the commercial objectives of these three city branding. They don't seem to know much about the intentions of city branding makers "to play with their consciousness".